A Synthetic Polymer Scaffold Reveals the Self‐Maintenance Strategies of Rat Glioma Stem Cells by Organization of the Advantageous Niche. (19th February 2016) - Tabu, Kouichi; Muramatsu, Nozomi; Mangani, Christian; Wu, Mei; Zhang, Rong; Kimura, Taichi; Terashima, Kazuo; Bizen, Norihisa; Kimura, Ryosuke; Wang, Wenqian; Murota, Yoshitaka; Kokubu, Yasuhiro; et al.
Abstract : Cancer stem cells (CSCs) are believed to be maintained within a microenvironmental niche. Here we used polymer microarrays for the rapid and efficient identification of glioma CSC (GSC) niche mimicries and identified a urethane‐based synthetic polymer, upon which two groups of niche components, namely extracellular matrices (ECMs) and iron are revealed. In cultures, side population (SP) cells, defined as GSCs in the rat C6 glioma cell line, are more efficiently sustained in the presence of their differentiated progenies expressing higher levels of ECMs and transferrin, while in xenografts, ECMs are supplied by the vascular endothelial cells (VECs), including SP cell‐derived ones with distinctively greater ability to retain xenobiotics than host VECs. Iron is stored in tumor infiltrating host macrophages (Mφs), whose protumoral activity is potently enhanced by SP cell‐secreted soluble factor(s). Finally, coexpression of ECM‐, iron‐, and Mφ‐related genes is found to be predictive of glioma patients' outcome. Our polymer‐based approach reveals the intrinsic capacities of GSCs, to adapt the environment to organize a self‐advantageous microenvironment niche, for their maintenance and expansion, which redefines the current concept of anti‐CSC niche therapy and has the potential to accelerate cancer therapy development. Stem Cells 2016;34:1151–1162 Abstract : Polymer microarray screening has identified a urethane‐based polymer PU10, which preferentially supports the growth of glioma stem cells (GSCs). ECM‐related protein galectin‐1 (Lgals1) and iron carrier protein transferrin (Tf) bound to PU10 have further unveiled two groups of niche components: (a) GSC‐derived vascular endothelial cells (VECs) supply ECMs and have distinctively greater ability to retain xenobiotics; (b) GSC‐secreted soluble factor(s) induce iron‐storing host‐derived macrophages (Mφs) infiltrated into tumors and potently enhance their protumoral activity. Tf is upregulated in non‐GSCs, and conversely its receptor TfR is upregulated in GSCs. Our polymer‐based approach reveals the intrinsic capacities of GSCs to self‐organize advantageous microenvironments for their maintenance and expansion. PU10: poly(tetramethylene glycol)2, 000 and 1, 3‐bis(isocyanatomethyl)cyclohexane (1:1)